Depenalization of the Threat of Death Penalty Sanctions for Perpetrators of Corrupt Criminal Acts Based on the Values of Justice - Bawono, Bambang Tri; Malik, Jamaludin (KnE Social Sciences, 2025)
Corruption is considered an extraordinary crime that has a negative impact on the economy, state stability, and public trust, damaging governance, public services, development, and social inequality. Based on Law Number 46 of 2009 concerning the Corruption Court, corruption cases must be tried in the Special Corruption Court within its jurisdiction. The focus of the study is to explain how the death penalty for corruption is constructed in the concept of legal certainty and how the depenalization of the threat of the death penalty for perpetrators of corruption are based on the value of justice. The purpose of this study is to determine and analyze the construction of the death penalty and the form of de-escalation of the threat of the death penalty for perpetrators of corruption. The research used a normative method (normative law research) and a normative case study in the form of legal behavior products and data obtained through literature studies. Emphasis was placed on secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Related to the context of legal certainty, the structure of the death penalty for corruption shows a significant discrepancy between the written legal standards and the applied judicial practices. According to Article 2 Paragraph 2 of Law Number 20 of 2001 concerning the Eradication of Corruption, perpetrators of corruption can be sentenced to death in several cases. However, the word “can” used in the provision indicates that the application of the death penalty is optional and not mandatory. Based on the value of justice, the depenalization policy is not always effective in protecting perpetrators of corruption from the threat of the death penalty. Because the death penalty is often considered inhumane and does not guarantee a reduction in the level of corruption, this policy is considered to better reflect human rights and substantive justice. Depenalization allows for a more constructive and reformist approach by emphasizing the recovery of state assets, prevention, and proportional punishment.